(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
At the present stage of the development of medicine, biological modeling of diseases is becoming the most important method of scientific knowledge, which necessitates the creation of such experimental models on laboratory animals that would most adequately reflect the mechanisms of the onset and development of human diseases, as well as the mechanisms of recovery. Setting up such experiments is unthinkable without a detailed knowledge of the biology of laboratory animals, which, being the most important part of the modeling experiment, remain poorly understood to date.